2006
DOI: 10.1103/physreve.74.046306
|View full text |Cite
|
Sign up to set email alerts
|

Producing droplets in parallel microfluidic systems

Abstract: We study the dynamics of two microfluidic droplets emitters placed in parallel. We observe complex dynamical behavior, including synchronization, quasiperiodicity, and chaos. This dynamics has a considerable impact on the properties of the resulting emulsions: chaotic and quasi-periodic regimes give rise to polydispersed emulsions with poorly controllable characteristics, whereas synchronized regimes generate well-controlled monodispersed emulsions. We derive a dynamical model that reproduces the trends observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 7 publications
1
66
0
Order By: Relevance
“…For massively parallel devices, however, these feedback effects become important even for flow rate driven devices, as these would typically be supplied from a single syringe pump. This manner of forcing would cause the flow rate at a particular junction to be set by the resistance through the entire parallel arm, so that device feedback can have a pronounced effect, as seen by Barbier et al (2006), even when all components of the system are incompressible. In designing parallel devices for monodisperse foam and emulsion formation, care must be taken to mitigate the downstream effects of bubbles or droplets on flow, especially at channel junctions (see Engl et al 2005;Jousse et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For massively parallel devices, however, these feedback effects become important even for flow rate driven devices, as these would typically be supplied from a single syringe pump. This manner of forcing would cause the flow rate at a particular junction to be set by the resistance through the entire parallel arm, so that device feedback can have a pronounced effect, as seen by Barbier et al (2006), even when all components of the system are incompressible. In designing parallel devices for monodisperse foam and emulsion formation, care must be taken to mitigate the downstream effects of bubbles or droplets on flow, especially at channel junctions (see Engl et al 2005;Jousse et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Designing massively parallel microfluidic channels is easy using current fabrication techniques, but the behaviour of microfluidic devices under highly parallel operation is poorly understood. Generating monodisperse foams and emulsions in parallel systems has proved challenging, in part due to the significant crosstalk and feedback in these systems (see, for instance, Barbier et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…In Electronic supplementary material The online version of this article (doi:10.1007/s10404-015-1651-8) contains supplementary material, which is available to authorized users. Najjaran 2012; Cristobal et al 2006;Link et al 2006;Zhou and Yao 2013;Barbier et al 2006;Fu et al 2014;Gleichmann et al 2014). Theoretical models are also proposed to explain and predict the dynamic behaviors of droplets, and thus provide better controlling of droplet traffic.…”
Section: Introductionmentioning
confidence: 99%
“…1932-1058/2013/7(3)/034112/13/$30.00 V C 2013 AIP Publishing LLC 7, 034112-1 that parallelization presents difficulties in flow control and fabrication complexity, demonstrated by Barbier et al, 12 Li et al, 13 and Mulligan and Rothstein. 14 Barbier et al 12 observed strong coupling in two parallel T-junctions, with complex dynamic behavior manifesting in synchronization, quasiperiodicity, and chaos.…”
Section: Introductionmentioning
confidence: 99%
“…As an added benefit, these extended distribution channels also serve to minimize crosstalk among orifices and make generation less susceptible to fluid disruptions by neighboring production and sources. 12,26 The distribution channels and orifices were narrowed to their current dimensions in order to increase the local velocities of the fluid flows, particularly of the continuous phase, at the flow-focusing regions, thereby elevating the capillary number to induce the geometry-controlled to dripping regime transition. The dependence of the mode of droplet formation on the capillary number-Ca ¼ gV/c EQ , where g is the viscosity and V is the superficial velocity of the continuous phase, and c EQ is the equilibrium surface tension between the continuous and dispersed phases-has been shown previously in studies utilizing flow-focusing devices.…”
Section: B Module Designmentioning
confidence: 99%